PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING BERBANTUAN MEDIA NEARPOD TERHADAP HASIL BELAJAR MURID PADA MATERI ENERGI DALAM KEHIDUPAN SEHARI-HARI KELAS IV SDN 1 KABILA - Dako, Fadhilatul Muna; Gamar Abdullah; Meylan Saleh; Kudus; Isnanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The research problem in this study is: “Is there any effect of the discovery learning model assisted by Nearpod media on students’ learning outcomes in the topic of energy in daily life in Grade IV of SDN 1 Kabila?” The objective of this study is to determine the effect of the discovery learning model assisted by Nearpod media on students’ learning outcomes in the topic of energy in daily life in Grade IV of SDN 1 Kabila. This study employed a quantitative approach using a pre-experimental method with a one-group pretest-posttest design. The population consisted of all fourth-grade students, with a sample of 20 students. Data collection techniques included observation, tests, and documentation. The results showed that the mean pretest score was 48.75, while the mean posttest score was 87.75. A comparison of the mean scores indicates that the posttest score was higher than the pretest score. Hypothesis testing was conducted using SPSS version 25.0, which showed that t-count = -21.250 > t-table = 1.725, or based on the significance value sig = 0.000 < α = 0.05. Therefore, it can be concluded that there is a significant effect of the discovery learning model assisted by Nearpod media on students’ learning outcomes in the topic of energy in daily life in Grade IV of SDN 1 Kabila.